minimal value of Binary Tree - haskell

I am trying to define a minTree function using foldTree define by:
foldTree :: (b -> a -> b -> b) -> b -> Tree a -> b
foldTree f e Leaf = e
foldTree f e (Node left x right) = f (foldTree f e left) x (foldTree f e right)
Here what I have so far.
minTree :: (Ord a) => Tree a -> Maybe a
minTree f e Leaf = e
minTree tree = foldTree f e tree
where
f x nothing = Just x
f x (Just y) = Just (min x y)
e = Nothing
But this code does not work and give a some error that I don't understand how to fix. Can someone help me to figure out what is wrong and how to fix it.

In your example b ~ Maybe a. This thus means that the first and the third parameter of f are Maybe as. You thus will need to check both. The second item is an a. Your f should thus determine the minimum of two Maybe as and an a, so something like:
minTree :: Ord a => Tree a -> Maybe a
minTree tree = foldTree f Nothing tree
where f Nothing y Nothing = Just y
f Nothing y (Just z) = …
f (Just x) y Nothing = …
f (Just x) y (Just z) = …
where I leave implementing the … parts as an exercise. Since a is a member of the Ord typeclass, you can work with min :: Ord a => a -> a -> a.

Related

How to define listTree so that it runs in linear time?

listTree' :: Tree a -> [a]
listTree' t = foldTree f z t []
where
f = undefined
z [] = []
Need help solving for f. when I insert f a b c = a ++ [b] ++ c I get an error
data Tree a
= Tip
| Bin (Tree a) a (Tree a)
deriving (Show, Eq)
foldTree :: (b -> a -> b -> b) -> b -> Tree a -> b
foldTree f z Tip = z
foldTree f z (Bin l x r) = f (foldTree f z l) x (foldTree f z r)
here is foldTree and data type for tree
In order to achieve linear time, you should let foldTree f z t return a function that takes a list and returns a list.
This means that for z, a leaf, we simply return the given list, and we thus do not prepend any value. For f we will take the list, call it with the right subtree, then prepend that list with the value of that Bin node, and finally call it with the left subtree, so:
listTree' :: Tree a -> [a]
listTree' t = foldTree f id t []
where f x y z ls = x (y: z ls)
Here ls is thus the list we need to process, z is a function to prepend the items of the right subtree to ls, y is the value stored in that node, and x is a function that prepends the items of the left subtree to the list.
We can define f, as #chi says as f x y z = x . (y:) . z. We thus first apply the function generated for the right subtree, then prepend the list with y, and then run it through the function of the left subtree.

Implementation of map on binary tree using fold

I'm struggling with define map over tree using foldBT. My idea is to convert the tree into list, map the operator over the list, and then convert the list back to tree. But it sounds inefficient and also doesn't make use of foldBT... I tried to run foldBT (*2) Nil (numTree [3,5,7] but ghci reported error. I don't really understand how the function foldBt works. An example would be great.
data SimpleBT a = Nil | N a (SimpleBT a) (SimpleBT a) deriving (Show, Eq)
foldBT :: (a -> b -> b -> b) -> b -> SimpleBT a -> b
foldBT f e Nil = e
foldBT f e (N a left right) = f a (foldBT f e left) (foldBT f e right)
mapTree :: (a -> b) -> SimpleBT a -> SimpleBT b
mapTree f Nil = Nil
mapTree f (N a left right) = N (f a) (mapTree f left) (mapTree f right)
size :: SimpleBT a -> Int
size Nil = 0
size (N _ left right) = 1 + size left + size right
insert :: SimpleBT a -> a -> SimpleBT a
insert Nil a = N a Nil Nil
insert (N x left right) a
| size left <= size right = N x (insert left a) right
| otherwise = N x left (insert right a)
numTree :: [a] -> SimpleBT a
numTree xs = foldl insert Nil xs
Let us hypothesize mapTree f = foldBT g e, and solve for g and e. The definition of foldBT says:
foldBT g e Nil = e
Meanwhile, from the definition of mapTree, we get:
mapTree f Nil = Nil
From our hypothesis that mapTree f = foldBT g e, we can transform the second equation and stick it next to the first equation:
foldBT g e Nil = Nil
foldBT g e Nil = e
So e = Nil.
Let's do the other clauses now. The definition of foldBT says:
foldBT g e (N a left right) = g a (foldBT g e left) (foldBT g e right)
Meanwhile, mapTree's definition says:
mapTree f (N a left right) = N (f a) (mapTree f left) (mapTree f right)
Again, using our hypothesis mapTree f = foldBT g e, we can now rewrite this equation, and stick it next to the first one:
foldBT g e (N a left right) = N (f a) (foldBT g e left) (foldBT g e right)
foldBT g e (N a left right) = g a (foldBT g e left) (foldBT g e right)
So g a = N (f a) would validate this equation. Writing these all down in one spot, we get:
mapTree f = foldBT g e where
e = Nil
g a = N (f a)
You can inline the definitions of e and g if you like; I would.
mapTree f = foldBT (N . f) Nil
The idea of the foldBT function is that it takes an argument for each constructor of your data type (plus the one holding the whole SimpleBT a itself that you wish to fold over). The first one, of type a -> b -> b -> b corresponds to the recursive N constructor, and shows how to combine the value at the node with the results of the fold of the two subtrees into the result of the entire fold. The second argument corresponds to the Nil constructor, and since this constructor takes no arguments, the corresponding argument to fold is simply a constant.
It's completely analagous to folding over a list. The list type [a] also has 2 constructors. One of them takes an a and a list and adds the element to the front of the list: a -> [a] -> [a], this gives rise to a "fold function" of type a -> b -> b. The other constructor, as in your case, is nullary (the empty list), so again corresponds to an argument whose type is just b. Hence foldr for a list has type (a -> b -> b) -> b -> [a] -> b.
There is a great discussion of this, with more examples, in this chapter of the Haskell wikibook: https://en.wikibooks.org/wiki/Haskell/Other_data_structures
As for how to build a map from a fold, for your particular tree type - bearing in mind what I've said above, you need (given a mapping function f :: a -> a0), we need to think about what this does to both the Nil tree, and what it does recursively to trees with a leaf and 2 branches. Also, since our return type will of course be another tree of the same type, b here will be SimpleBT a0.
For Nil, obviously we want map to leave it unchanged, so the second argument to foldBT will be Nil. And for the other constructor, we want the map to apply the base function to the value at the leaf, and then recursively map over the 2 branches. This leads us to the function \a left right -> N (f a) (mapTree f left) (mapTree f right).
So we can conclude that the map function can be defined as follows (thanks to #DanielWagner and #WillemVanOnsen for helping me fix my first broken version):
mapTree :: (a -> b) -> SimpleBT a -> SimpleBT b
mapTree f = foldBT foldFunc Nil
where foldFunc a l r = N (f a) l r

A traversal as data

I heard about this construction which is loosely described as “a traversal represented in data, applied to some structure, without the need for the applicative”
It can be defined as:
data X a b r =
| Done r
| Step a (X a b (b -> r))
A word description would be as follows:
the type X a b r describes the shape of a structure
which contains things of type a
and for each a you get the opportunity to produce something of type b
and provided you do that for each a,
you get something of type r.
Thus a “traversal” of a list, [a], has type X a b [b], because if you can turn each a of the list into a b then you get a [b].
My question is: what is this thing called? Is there a reference to more information about it?
Example usage:
instance Functor (X a b) where
fmap f (Done r) = f r
fmap f (Step a next) = Step a (fmap (f .) next)
f :: [a] -> X a b [b]
f [] = Done []
f (a:as) = Step a (fmap (flip (:)) as)
g :: Applicative f => (a -> f b) -> X a b r -> f r
g f (Done r) = pure r
g f (Step a next) = g f next <*> f a
More generally:
instance Applicative (X a b) where
pure x = Done x
Done f <*> y = fmap (\y -> f y) y
Step a next <*> y = Step a (fmap flip next <*> y)
t :: Traversable t => t a -> X a b (t b)
t = traverse (\a -> Step a (Done id))
And, assuming I haven’t made any errors, we should find that:
flip g . t == traverse
Edit: I’ve thought about this some more. There is something this doesn’t have which a traversal has: a traversal can split up the computation into something that isn’t “one at a time,” for example to traverse a binary tree one can traverse the left and right half “in parallel.” Here is a structure that I think gives the same effect:
data Y a b r =
| Done r
| One a (b -> r)
| forall s t. Split (Y a b s) (Y a b t) (s -> t -> r)
(Slightly vague syntax as I don’t remember it and don’t want to write this as a gadt)
f1 :: X a b r -> Y a b r
f1 (Done x) = Done x
f1 (Step a next) = Split (One a id) (f1 next) (flip ($))
f2 :: Y a b r -> X a b r
f2 (Done x) = Done x
f2 (One a f) = Step a (Done f)
f2 (Split x y f) = f <$> f2 x <*> f2 y

Haskell: Folding over trees

I am going through some old courses online and came across this task:
data Tree a = Leaf
| Branch a (Tree a) (Tree a)
deriving (Show, Eq)
fold :: (a -> b -> b -> b) -> b -> Tree a -> b
fold _ acc Leaf = acc
fold f acc (Branch v l r) = f v (fold f acc l) (fold f acc r)
foldRT :: (a -> b -> b) -> b -> Tree a -> b
foldRT _ acc Leaf = acc
foldRT f acc (Branch v l r) = foldRT f (f v (foldRT f acc r)) l
The task is to rewrite foldRT in terms of fold. I have been stuck on it for ages and can't wrap my head around it.
A walk through would be greatly appreciated.
As its name and type signature suggest, foldRT is a bona fide right fold for your tree (you can convince yourself of that by hand-evaluating it for something like Branch 1 (Branch 0 Leaf Leaf) (Branch 2 Leaf Leaf)). That means implementing Foldable will give you foldRT: foldRT = foldr. Why is that relevant? Because, in this case, it is much easier to implement foldMap than it is to figure out how to write foldr directly:
-- Note that l and r here aren't the subtrees, but the results of folding them.
instance Foldable Tree where
foldMap f = fold (\v l r -> l <> f v <> r) mempty
If you want to write foldRT without relying on a Foldable instance, all you need is expanding the foldMap-based definition of foldr (see the answers to this question for the details I'll gloss over here):
foldRT f z t = appEndo (foldMap (Endo . f) t) z
-- To make things less clumsy, let's use:
foldEndo f = appEndo . foldMap (Endo . f)
-- foldEndo f = flip (foldRT f)
foldEndo f = appEndo . fold (\v l r -> l <> Endo (f v) <> r) mempty
-- As we aren't mentioning foldMap anymore, we can drop the Endo wrappers.
-- mempty #(Endo _) = Endo id
-- Endo g <> Endo f = Endo (g . f)
foldEndo f = fold (\v l r -> l . f v . r) id
-- Bringing it all back home:
foldRT :: (a -> b -> b) -> b -> Tree a -> b
foldRT f z t = fold (\v l r -> l . f v . r) id t z
(Note that we ultimately reached a solution of the sort suggested by Carl, only through an indirect route.)

Histomorphisms, Zygomorphisms and Futumorphisms specialised to lists

I ended up figuring it out. See the video and slides of a talk I gave:
slides/pdf
video
Original question:
In my effort to understand generic recursion schemes (i.e., that use Fix) I have found it useful to write list-only versions of the various schemes. It makes it much easier to understand the actual schemes (without the additional overhead of the Fix stuff).
However, I have not yet figured out how to define list-only versions of zygo and futu.
Here are my specialised definitions so far:
cataL :: (a -> b -> b) -> b -> [a] -> b
cataL f b (a : as) = f a (cataL f b as)
cataL _ b [] = b
paraL :: (a -> [a] -> b -> b) -> b -> [a] -> b
paraL f b (a : as) = f a as (paraL f b as)
paraL _ b [] = b
-- TODO: histo
-- DONE: zygo (see below)
anaL :: (b -> (a, b)) -> b -> [a]
anaL f b = let (a, b') = f b in a : anaL f b'
anaL' :: (b -> Maybe (a, b)) -> b -> [a]
anaL' f b = case f b of
Just (a, b') -> a : anaL' f b'
Nothing -> []
apoL :: ([b] -> Maybe (a, Either [b] [a])) -> [b] -> [a]
apoL f b = case f b of
Nothing -> []
Just (x, Left c) -> x : apoL f c
Just (x, Right e) -> x : e
-- DONE: futu (see below)
hyloL :: (a -> c -> c) -> c -> (b -> Maybe (a, b)) -> b -> c
hyloL f z g = cataL f z . anaL' g
hyloL' :: (a -> c -> c) -> c -> (c -> Maybe (a, c)) -> c
hyloL' f z g = case g z of
Nothing -> z
Just (x,z') -> f x (hyloL' f z' g)
How do you define histo, zygo and futu for lists?
Zygomorphism is the high-falutin' mathsy name we give to folds built from two semi-mutually recursive functions. I'll give an example.
Imagine a function pm :: [Int] -> Int (for plus-minus) which intersperses + and - alternately through a list of numbers, such that pm [v,w,x,y,z] = v - (w + (x - (y + z))). You can write it out using primitive recursion:
lengthEven :: [a] -> Bool
lengthEven = even . length
pm0 [] = 0
pm0 (x:xs) = if lengthEven xs
then x - pm0 xs
else x + pm0 xs
Clearly pm0 is not compositional - you need to inspect the length of the whole list at each position to determine whether you're adding or subtracting. Paramorphism models primitive recursion of this sort, when the folding function needs to traverse the whole subtree at each iteration of the fold. So we can at least rewrite the code to conform to an established pattern.
paraL :: (a -> [a] -> b -> b) -> b -> [a] -> b
paraL f z [] = z
paraL f z (x:xs) = f x xs (paraL f z xs)
pm1 = paraL (\x xs acc -> if lengthEven xs then x - acc else x + acc) 0
But this is inefficient. lengthEven traverses the whole list at each iteration of the paramorphism resulting in an O(n2) algorithm.
We can make progress by noting that both lengthEven and para can be expressed as a catamorphism with foldr...
cataL = foldr
lengthEven' = cataL (\_ p -> not p) True
paraL' f z = snd . cataL (\x (xs, acc) -> (x:xs, f x xs acc)) ([], z)
... which suggests that we may be able to fuse the two operations into a single pass over the list.
pm2 = snd . cataL (\x (isEven, total) -> (not isEven, if isEven
then x - total
else x + total)) (True, 0)
We had a fold which depended on the result of another fold, and we were able to fuse them into one traversal of the list. Zygomorphism captures exactly this pattern.
zygoL :: (a -> b -> b) -> -- a folding function
(a -> b -> c -> c) -> -- a folding function which depends on the result of the other fold
b -> c -> -- zeroes for the two folds
[a] -> c
zygoL f g z e = snd . cataL (\x (p, q) -> (f x p, g x p q)) (z, e)
On each iteration of the fold, f sees its answer from the last iteration as in a catamorphism, but g gets to see both functions' answers. g entangles itself with f.
We'll write pm as a zygomorphism by using the first folding function to count whether the list is even or odd in length and the second one to calculate the total.
pm3 = zygoL (\_ p -> not p) (\x isEven total -> if isEven
then x - total
else x + total) True 0
This is classic functional programming style. We have a higher order function doing the heavy lifting of consuming the list; all we had to do was plug in the logic to aggregate results. The construction evidently terminates (you need only prove termination for foldr), and it's more efficient than the original hand-written version to boot.
Aside: #AlexR points out in the comments that zygomorphism has a big sister called mutumorphism, which captures mutual recursion in all
its glory. mutu generalises zygo in that both the folding
functions are allowed to inspect the other's result from the previous
iteration.
mutuL :: (a -> b -> c -> b) ->
(a -> b -> c -> c) ->
b -> c ->
[a] -> c
mutuL f g z e = snd . cataL (\x (p, q) -> (f x p q, g x p q)) (z, e)
You recover zygo from mutu simply by ignoring the extra argument.
zygoL f = mutuL (\x p q -> f x p)
Of course, all of these folding patterns generalise from lists to the fixed point of an arbitrary functor:
newtype Fix f = Fix { unFix :: f (Fix f) }
cata :: Functor f => (f a -> a) -> Fix f -> a
cata f = f . fmap (cata f) . unFix
para :: Functor f => (f (Fix f, a) -> a) -> Fix f -> a
para f = snd . cata (\x -> (Fix $ fmap fst x, f x))
zygo :: Functor f => (f b -> b) -> (f (b, a) -> a) -> Fix f -> a
zygo f g = snd . cata (\x -> (f $ fmap fst x, g x))
mutu :: Functor f => (f (b, a) -> b) -> (f (b, a) -> a) -> Fix f -> a
mutu f g = snd . cata (\x -> (f x, g x))
Compare the definition of zygo with that of zygoL. Also note that zygo Fix = para, and that the latter three folds can be implemented in terms of cata. In foldology everything is related to everything else.
You can recover the list version from the generalised version.
data ListF a r = Nil_ | Cons_ a r deriving Functor
type List a = Fix (ListF a)
zygoL' :: (a -> b -> b) -> (a -> b -> c -> c) -> b -> c -> List a -> c
zygoL' f g z e = zygo k l
where k Nil_ = z
k (Cons_ x y) = f x y
l Nil_ = e
l (Cons_ x (y, z)) = g x y z
pm4 = zygoL' (\_ p -> not p) (\x isEven total -> if isEven
then x - total
else x + total) True 0
Histomorphism models dynamic programming, the technique of tabulating the results of previous subcomputations. (It's sometimes called course-of-value induction.) In a histomorphism, the folding function has access to a table of the results of earlier iterations of the fold. Compare this with the catamorphism, where the folding function can only see the result of the last iteration. The histomorphism has the benefit of hindsight - you can see all of history.
Here's the idea. As we consume the input list, the folding algebra will output a sequence of bs. histo will jot down each b as it emerges, attaching it to the table of results. The number of items in the history is equal to the number of list layers you've processed - by the time you've torn down the whole list, the history of your operation will have a length equal to that of the list.
This is what the history of iterating a list(ory) looks like:
data History a b = Ancient b | Age a b (History a b)
History is a list of pairs of things and results, with an extra result at the end corresponding to the []-thing. We'll pair up each layer of the input list with its corresponding result.
cataL = foldr
history :: (a -> History a b -> b) -> b -> [a] -> History a b
history f z = cataL (\x h -> Age x (f x h) h) (Ancient z)
Once you've folded up the whole list from right to left, your final result will be at the top of the stack.
headH :: History a b -> b
headH (Ancient x) = x
headH (Age _ x _) = x
histoL :: (a -> History a b -> b) -> b -> [a] -> b
histoL f z = headH . history f z
(It happens that History a is a comonad, but headH (née extract) is all we need to define histoL.)
History labels each layer of the input list with its corresponding result. The cofree comonad captures the pattern of labelling each layer of an arbitrary structure.
data Cofree f a = Cofree { headC :: a, tailC :: f (Cofree f a) }
(I came up with History by plugging ListF into Cofree and simplifying.)
Compare this with the free monad,
data Free f a = Free (f (Free f a))
| Return a
Free is a coproduct type; Cofree is a product type. Free layers up a lasagne of fs, with values a at the bottom of the lasagne. Cofree layers up the lasagne with values a at each layer. Free monads are generalised externally-labelled trees; cofree comonads are generalised internally-labelled trees.
With Cofree in hand, we can generalise from lists to the fixpoint of an arbitrary functor,
newtype Fix f = Fix { unFix :: f (Fix f) }
cata :: Functor f => (f b -> b) -> Fix f -> b
cata f = f . fmap (cata f) . unFix
histo :: Functor f => (f (Cofree f b) -> b) -> Fix f -> b
histo f = headC . cata (\x -> Cofree (f x) x)
and once more recover the list version.
data ListF a r = Nil_ | Cons_ a r deriving Functor
type List a = Fix (ListF a)
type History' a b = Cofree (ListF a) b
histoL' :: (a -> History' a b -> b) -> b -> List a -> b
histoL' f z = histo g
where g Nil_ = z
g (Cons_ x h) = f x h
Aside: histo is the dual of futu. Look at their types.
histo :: Functor f => (f (Cofree f a) -> a) -> (Fix f -> a)
futu :: Functor f => (a -> f (Free f a)) -> (a -> Fix f)
futu is histo with the arrows flipped and with Free replaced by
Cofree. Histomorphisms see the past; futumorphisms predict the future.
And much like cata f . ana g can be fused into a hylomorphism,
histo f . futu g can be fused into a
chronomorphism.
Even if you skip the mathsy parts, this paper by Hinze and Wu features a good, example-driven tutorial on histomorphisms and their usage.
Since no one else has answered for futu yet, I'll try to stumble my way through. I'm going to use ListF a b = Base [a] = ConsF a b | NilF
Taking the type in recursion-schemes: futu :: Unfoldable t => (a -> Base t (Free (Base t) a)) -> a -> t.
I'm going to ignore the Unfoldable constraint and substitute [b] in for t.
(a -> Base [b] (Free (Base [b]) a)) -> a -> [b]
(a -> ListF b (Free (ListF b) a)) -> a -> [b]
Free (ListF b) a) is a list, possibly with an a-typed hole at the end. This means that it's isomorphic to ([b], Maybe a). So now we have:
(a -> ListF b ([b], Maybe a)) -> a -> [b]
Eliminating the last ListF, noticing that ListF a b is isomorphic to Maybe (a, b):
(a -> Maybe (b, ([b], Maybe a))) -> a -> [b]
Now, I'm pretty sure that playing type-tetris leads to the only sensible implementation:
futuL f x = case f x of
Nothing -> []
Just (y, (ys, mz)) -> y : (ys ++ fz)
where fz = case mz of
Nothing -> []
Just z -> futuL f z
Summarizing the resulting function, futuL takes a seed value and a function which may produce at least one result, and possibly a new seed value if it produced a result.
At first I thought this was equivalent to
notFutuL :: (a -> ([b], Maybe a)) -> a -> [b]
notFutuL f x = case f x of
(ys, mx) -> ys ++ case mx of
Nothing -> []
Just x' -> notFutuL f x'
And in practice, perhaps it is, more or less, but the one significant difference is that the real futu guarantees productivity (i.e. if f always returns, you will never be stuck waiting forever for the next list element).

Resources